A Corpus-Driven Pragmatic Analysis of Verb Presupposition Triggers in The Great Gatsby: A Cross-Linguistic Perspective - Yitong Duan (International Journal of Education and Humanities, 2026)
The Great Gatsby by F. Scott Fitzgerald has been extensively examined from literary and stylistic perspectives; however, its pragmatic dimensions, particularly verb presupposition triggers, remain underexplored. Factive and implicative verbs play a crucial role in conveying implicit assumptions, shaping narrative meaning, and maintaining discourse coherence. The lack of corpus-based pragmatic analysis limits a comprehensive understanding of how presuppositional mechanisms operate within literary texts, especially in cross-linguistic contexts. This study aims to identify and classify verb presupposition triggers in The Great Gatsby, with a specific focus on factive and implicative verbs, and to examine how these triggers contribute to the construction of implicit meaning and narrative coherence. Additionally, the study seeks to propose a cross-linguistic, corpus-driven framework for presupposition analysis. A corpus-driven approach is employed by aligning the English source text of The Great Gatsby with its Chinese translations. The analysis draws on an established corpus of verb presupposition triggers in modern Chinese, enabling the systematic identification and classification of corresponding presuppositional verbs in English through cross-linguistic mapping. The findings reveal that factive and implicative verbs function as key pragmatic devices that embed background assumptions, guide reader interpretation, and enhance textual cohesion throughout the narrative. The corpus-based, cross-linguistic methodology proves effective in uncovering implicit pragmatic patterns that are not easily detected through traditional qualitative analysis. This study enriches the pragmatic interpretation of The Great Gatsby and demonstrates the value of corpus-driven methods in literary pragmatics. Moreover, it offers a replicable methodological model for constructing verb presupposition trigger corpora in English and other languages, contributing to broader research in corpus pragmatics and cross-linguistic studies